Synthesis, biodistribution and antitumor activity of hematoporphyrin-platinum(II) conjugates - Kim, YS; Song, R; Kim, DH; Jun, MJ; Sohn, YS (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
A new series of platinum(II) complexes of pegylated hematoporphyrin derivatives with controlled hydrophobic/hydrophilic balance were synthesized by introducing different kinds of poly(ethylene glycol) and amine ligands to the porphyrin ring. The antitumor activity of the porphyrin-platinum(II) conjugates was assayed in vitro and in vivo against leukemia L1210 cell line and various human tumor cell lines. The present complexes exhibited high antitumor activity and improved water solubility as well as considerable lipophilicity. In particular, complex 16 showed not only higher in vivo activity (T/C% = 258) than. cisplatin (T/C% = 184) and carboplatin (T/C% = 168), but also excellent solubility in water and organic solvent. The antitumor activity of complex 20 was superior to that of carboplatin against all human tumor cell lines tested. Moreover, some amphiphilic complexes (7 and 12) exhibited elevated tumor-localizing effect (tumor/muscle ratio > 2). (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: PHOTODYNAMIC THERAPY; TUMOR; PHOTOSENSITIZERS; PORPHYRIN; DELIVERY; SERIES; COMPLEXES; EFFICACY; DESIGN; FOLATE